Switching from monoculture to polyculture farming benefits birds in oil palm production landscapes: evidence from mist netting data - Yahya, Muhammad S.; Syafiq, Muhamad; Ashton‐Butt, Adham; Ghazali, Amal; Asmah, Siti; Azhar, Badrul (John Wiley & Sons, 2017)
Monoculture farming is pervasive in industrial oil palm agriculture, including those RSPO plantations certified as sustainably managed. This farming practice does not promote the maintenance of farmland biodiversity. However, little scientific attention has been given to polyculture farming in oil palm production landscapes. Polyculture farming is likely to increase the floristic diversity and stand structural complexity that underpins biodiversity. Mist nets were used to sample birds at 120 smallholdings in Peninsular Malaysia. At each site, 12 vegetation structure characteristics were measured. We compared bird species richness, abundance, and composition between monoculture and polyculture smallholdings and used predictive models to examine the effects of habitat quality on avian biodiversity. Bird species richness was significantly greater in polyculture than that of monoculture smallholdings. The number of fallen and standing, dead oil palms were also important positive predictors of species richness. Bird abundance was also strongly increased by standing and dead oil palms and decreased with oil palm stand height. Our results indicate that polyculture farming can improve bird species richness in oil palm production landscapes. In addition, key habitat variables that are closely associated with farming practices, such as the removal of dead trees, should and can be managed by oil palm growers in order to promote biodiversity. To increase the sustainability of oil palm agriculture, it is imperative that stakeholders modify the way oil palms are currently planted and managed. Our findings can guide policy makers and certification bodies to promote oil palm production landscapes that will function more sustainably and increase existing biodiversity of oil palm landscapes.